Prevalence, Awareness and Control of Hypertension in a Well-Educated Professional Group in Nepal - Gautam, Mani Prasad; Ghimire, Usha; Shrestha, Krishna Maya; Paudel, Bijaya; Khatiwada, Prakash; Adhikari, Bhojraj (Nepalese Heart Journal, 2017)
Background and Aims: Hypertension continues to be the major modifiable risk factor leading to premature death due to cardiovascular diseases. Therefore awareness, timely diagnosis, treatment and control of hypertension in primary care are crucial for reducing disease burden. In this respect, authentic data on these issues are paramount of importance. The aim of this study was to address this gap in a well-educated group of Nepalese subjects.Methods: A cross-sectional study in the delegates of the national level meeting of a professional group - lawyers was conducted in 2015 February. Standard criteria were used to define hypertension and blood pressure goal. Awareness and treatment were based on self-report.Results: A total of 249 subjects were included in the study. The prevalence of hypertension was 18.88%. Among hypertensive, 70% subjects were newly detected and they were unaware of their blood pressure status before. Remaining 30% were known cases of hypertension and among them only 64% were on medicine and 36% were not despite awareness of hypertension. Only 55.5% of them on medicine had achieved blood pressure goal.Conclusion: The scenario of hypertension in Nepal even in educated group is very alarming with majority of them being unaware of the hypertension status, more than one third not taking medicine and nearly half on medicine not achieving desired blood pressure goal. From this, the situation obviously seems more warning in general population and needs well-designed assessment.Nepalese Heart Journal 2017; 14(1): 21-24